A Parsonage-Turner Syndrome secondary to Parvovirus B19 infection - Mozzani, Flavio; Marino, Noemi Giuliana; Becciolini, Andrea; Di Donato, Eleonora; Ariani, Alarico; Santilli, Daniele (Acta Biomedica Atenei Parmensis, 2021)
Parvovirus B19 (PVB19) is a small DNA virus that causes the fifth disease in children; however it can also affect adults. The infection can be asymptomatic in about a quarter of healthy subjects. Typical clinical manifestations are: short lived fever accompanied by asthenia, myalgias and pharyngodynia; symmetrical acute polyarthritis; megalo-erytema in child; maculopulotic rash and/or fleeting purpuric at the extremities in adult; adenopathies in the cervical area. Atypical manifestions can affect neurological system (both central and peripheral), hearth and kidney. We describe a 37-year-old man with neuralgic amyotrophy (Parsonage-Turner syndrome) caused by Parvovirus B19 infection.